DESIGN AND CONSTRUCTION OF A CORN SHELLING MACHINE WITH A CAPACITY OF 80KG/HOUR USING A COMBO ENGINE - Samuel Haris Purba; Saut Pardede (Journal of Golden Generation Engineering, 2025)
This study discusses the design and construction of a corn sheller with a capacity of 80 kg/hour using an internal combustion engine . A corn sheller is a machine that functions to shell corn to separate the corn kernels from the corn cobs. In Indonesia, corn is available in abundance in rural areas, especially during the harvest season. In the production process, generally, during the shelling process, many farmers still use the shelling method by hand or using simple tools, which takes quite a long time. The reason people still use the shelling method by hand or using tools is because the price of the machine is too expensive and they are not even aware of the existence of a corn shelling machine. This corn shelling machine with a 5.5 HP internal combustion engine is a tool designed to speed up and simplify the corn shelling process efficiently and produce a fairly large production capacity of 80 kg / hour. To extend the service life of this corn shelling machine, maintenance and cleanliness should be carried out so that the machine can operate optimally without problems. Safety also needs to be considered to avoid unexpected work accidents.